2016
DOI: 10.1142/s0578563416400180
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Embankment Reinforcement by Steel Sheet Pile Structure Against Tsunami Overflow

Abstract: This study proposes a new embankment reinforcement using steel sheet piles against tsunami overflow, which has been known as the main cause of the failures of the embankments by the 2011 Tohoku Earthquake Tsunami. Effectiveness of the proposed technique was discussed through a hydraulic experiment. A model of embankment was set in a horizontal open channel, and one or two steel plates are installed into the embankment from the top as vertical walls inside. Temporal variations of the shapes of the embankment an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…As a preliminary investigation of debris damming, the transient nature of coastal flooding was not considered herein. However, comparing to tsunamis, the time scale of the local flow conditions, in field studies of tsunami-stricken areas, (~7 min at prototype scale) is significantly shorter than the tsunami wave period (>10 min) [38]. The flow velocities at prototype scale (2-7 m/s) in these tests compared well to the velocities observed in the 2004 Indian Ocean Tsunami (2-5 m/s) [39].…”
Section: Debris Geometrysupporting
confidence: 53%
See 1 more Smart Citation
“…As a preliminary investigation of debris damming, the transient nature of coastal flooding was not considered herein. However, comparing to tsunamis, the time scale of the local flow conditions, in field studies of tsunami-stricken areas, (~7 min at prototype scale) is significantly shorter than the tsunami wave period (>10 min) [38]. The flow velocities at prototype scale (2-7 m/s) in these tests compared well to the velocities observed in the 2004 Indian Ocean Tsunami (2-5 m/s) [39].…”
Section: Debris Geometrysupporting
confidence: 53%
“…The cases with a single shipping container consistently formed a dam with similar characteristics and loads, whereas the characteristics of the hydro pole and boards varied between trials. Bocchiola et al [38] discussed the importance of the "key" log in the formation of a debris dam. The "key" log refers to the first object to get caught on the obstacle and initiates the formation of the dam.…”
Section: Debris Geometrymentioning
confidence: 99%
“…Sheet piles and concrete screens in the crestline improve the stability of the dike and help controlling seepage [1,6]. In case of an overflow or overtopping event and consequent erosion of the landside slope, the height of the dike and with this the flood protection function are still ensured when applying sheet piles [101].…”
Section: Overviewmentioning
confidence: 99%
“…A significant onsite evaluation was carried out by Hou et al [18] at a major dock project in Shanghai, assessing the deformation characteristics of a large-span DSSP cofferdam. Investigations into DSSP efficacy against tsunami impacts were undertaken by Furuichi et al [6] and Mitobe et al [19], who demonstrated superior resistance of double-walled configurations in flume tests. Zhu et al [20] applied the Bayesian approach to enhance the reliability assessment of DSSPs, integrating both statistical and field data effectively.…”
Section: Introductionmentioning
confidence: 99%